Numerical study of bending test on compacted clay by Discrete Element Method: tensile strength determination. (27th January 2009) - Ammeri, Abdelkader; Jamei, Mehrez; Bouassida, Mounir; Ple, Olivier; Villard, Pascal; Gourc, Jean-Pierre
In order to study the tensile compacted clay behaviour, a series of laboratory bending tests were carried out. The analysis of the results and the determination of the relevant parameters are difficult. Different numerical simulations using Discrete Element Method (DEM) were performed and compared with analytical differential model, which seems to be the most suitable to interpret bending test results for the clay soils. The DEM confirms that the compression stress remains a linear function until the failure. However, the tensile stresses increase as a non-linear function. The differential model remains efficient only when the tensile strain field is well measured.